2012
DOI: 10.1007/s00404-012-2633-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infertility and infertility duration on female sexual functions

Abstract: As the infertility duration extends, the scores of all parameters, except sexual satisfaction, decreases. But as many factors play a role in female sexual dysfunction, to blame prolonged infertility as a situation that negatively affects female sexual life, prospectively designed studies should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 12 publications
8
41
1
1
Order By: Relevance
“…In the literature, there are limited studies looking at duration of infertility and sexual impact or sexual dysfunction. One study by Iris et al 28 found that all measurements of sexual function decreased with the exception of sexual satisfaction. The fact that this study was performed in Turkey makes it difficult to compare because the social, psychological, and marital implications of infertility differ significantly across different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are limited studies looking at duration of infertility and sexual impact or sexual dysfunction. One study by Iris et al 28 found that all measurements of sexual function decreased with the exception of sexual satisfaction. The fact that this study was performed in Turkey makes it difficult to compare because the social, psychological, and marital implications of infertility differ significantly across different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados são condizentes com os de outros estudos, que utilizaram o mesmo instrumento e não encontraram diferenças na função sexual de mulheres inférteis comparadas às férteis 14,15,20,24 . Outras análises que avaliaram somente mulheres inférteis também não encontraram diferenças 22,25 , mas outros autores identificaram disfunção sexual em mulheres infér-teis 1,2,5,16,[26][27][28][29] . Além disso, mulheres com infertilidade secundária apresentam menor comprometimento da função sexual nesse grupo de mulheres com infertilidade primária 18 .…”
Section: Discussionunclassified
“…Higher rates were found in a study from Poland. Here, the authors proposed that the crucial factor might be the duration of the partnership and not of the fertility disorder [8]. The response rate of this survey was 37%.…”
Section: Prevalence Of Sexual Disorders In Infertile Couplesmentioning
confidence: 95%